The Effect of the Fraud Pentagon on Fraudulent Financial Statements and Their Impact on Funding Decisions - Nur Hidayah Kusumaningrum Fadhilah; Muhammad Zulvan Dwi Hatmoko; Meutia Riany; Ucu Tuti Alawiyah; Khairul Mujahidi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The purpose of this study is to test whether financial targets, ineffective monitoring, change in auditors, change in directors, frequent number of CEO's pictures affect fraudulent financial statements and their impact on funding decisions in all non-financial companies listed on the Indonesia Stock Exchange (IDX) and sanctioned by OJK for violating regulation No. VIII.G.7 from 2010 to 2021. The data used in this study are secondary data derived from financial reports published by the company. A total of 54 companies became the population in the study. The sample selection in this study used a purposive sampling technique with certain criteria and 9 companies were selected as research samples. The data analysis technique in this study is using panel data regression with the help of Eviews software version 12. The results of this study indicate that simultaneously financial targets, ineffective monitoring, change in auditors, change in directors and frequent number of CEO's pictures have no effect on fraudulent financial statements in all companies listed on the Indonesia Stock Exchange (IDX) from 2010 to 2021. Furthermore, fraudulent financial statements affect funding decisions. Partially, financial targets, changes in directors, and frequent numbers of CEO's pictures have no significant effect on fraudulent financial statements. Meanwhile, change in auditor and ineffective monitoring have a negative and significant effect on fraudulent financial statements in all companies listed on the Indonesia Stock Exchange (IDX) from 2010 to 2021.